Characteristics and Classification of Arid Region Soils: Salt Lake Specially Protected Area (Tuz GÖlü-Turkey) - DENGIZ, ORHAN (Asian Journal of Chemistry, 2010)
Salt lake is a unique ecosystem for both agricultural activities and natural life in Turkey. This study was aimed to determine chemical and physical properties and classifying soils of salt lake (Tuz Gölü) specially protected area. The study revealed presence of 13 great groups in salt lake (Tuz Gölü) specially protected area. Soils determined were classified as entisol (26.7 %), aridisol (47.2 %), vertisol (0.6 %), histosol (0.3 %) according to soil taxonomy. Soil organic matter (SOM) for a depth of the upper horizons ranged from 0.64 to 4.49 % except for SOM-rich histic epipedon (67.8%). Bulk density of the soils varied between 0.12 to1.56 g cm-3. High clay content of the soils ranging from 68.4 to 10.72% for the entire horizons causes poor drainage conditions in about 16.4% of the salt lake (Tuz Gölü) specially protected area. Sustainability of prime farmlands of the salt lake (Tuz Gölü) specially protected area can be ensured by best management practices such as reduce tillage, residue incorporation, surface and subsurface drainage, windbreaks, rotational cultivation, ecologically suitable crop selection, integrated pest management and intercropping.